APPLICATION OF COUNTING BOARD LEARNING MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN ELEMENTARY/MI ELEMENTARY SCHOOL ADDITION AND WHOLE NUMBERS MATERIAL - Suleman, Muh Asharif; Idayanti, Zulfi; Basri, B; Shaleh, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research aims to improve student learning outcomes regarding addition and whole numbers using counting board learning media. This research is experimental, with the research design being a pretest-posttest control group design. The population in this study were all class II students of MIS Asy-Syafi'iyah Kendari. The research sample was determined using a purposive sampling technique, with class II A as the control class and class II B as the experimental class. Data collection techniques use observation, tests, and documentation. The data analysis techniques used are descriptive and inferential analysis. The research results showed a significant difference between the learning outcomes of experimental class and control class students after treatment, where t_count was 2.329 > t_table 2.006, with the N-Gain test results in the experimental class being 63.78% in the quite effective category. Based on the results of this research, the counting board learning medium is quite effective for use in improving student learning outcomes, especially material for addition and whole numbers for class II SD/MI.